Developing a Proof-of-Concept Selection Test for Entry into Primary Teacher Education Programs - Robert Klassen; Tracy Durksen; Lisa E Kim; Fiona Patterson; Emma Rowett; Jane Warwick; Paul Warwick; Mary Anne Wolpert (International Journal of Assessment Tools in Education)
The purpose of this article is to report on the development of a proof-of-concept situational judgment test (SJT) to assist in the selection of candidates for primary teacher education (ITE) programs. Nine development steps involving practising teachers, teacher educators, and applicants to ITE programs were carried out to establish target attributes and to develop content for the test. The results from administering the test to 124 primary ITE candidates showed a near-normal distribution, high levels of reliability, and significant positive correlations with a range of concurrently administered interview scores. We conclude with a description of the necessary next steps needed to implement evidence-supported teacher education selection processes in a range of international settings.